Investigating the Challenges Confronting Vocational Education in Botswana and Potential Remedies: An Empirical Study - Oshima, Mmolai Samuel; Ushe, Makambe; Jerald, Hondonga (Journal of Technical Education and Training, 2023)
The importance of vocational education for improving national human capital cannot be underscored. Yet, its objective of improving the quality and quantity of human capital has yet to be fully achieved due to its shortcomings. The training system's significant challenges have yet to be determined and explored to develop appropriate interventions. This study examined the challenges bedevilling vocational education in Botswana, leading to its failure to execute its mandate fully. The paper followed a positivist paradigm whereby a survey design was adopted with the quantitative methodology used to collect data using a questionnaire administered to 61 respondents. Data was analysed using the Statistical Package for Social Sciences (SPSS), producing descriptive and inferential statistics. The study results revealed many challenges facing vocational education in Botswana, such as the lack of quality instructors and ineffective delivery, lack of finance leading to low-salaried teachers who are not motivated and lack of adequate infrastructure, among others.  It is, therefore, imperative for policymakers to consider the findings of this study to develop more effective strategies for enhancing the delivery of vocational education in the country to avoid wastage of limited resources.